Pedagogical Competence: Effective Communication of Students of Primary School Teacher Education of Universitas Terbuka in Palembang - Saputra, Alpin Herman; Anthony, Steven (Universitas Pahlawan Tuanku Tambusai, 2021)
Teacher is the party who is responsible for continuity of effective communication in learning so the teacher is urged to have a good communicative competence with students in order to obtain effective learning process. In this study teacher is students of primary school teacher education who has worked as a teacher (in-service training) or educator. This study is aimed to know how the competence of teacher in communicating effectively to the students. The research method used is mix research method (Survey and Thematic Qualitative). As a result, the level of effective communicative competence of students of primary school teacher education of UT who are also as teacher of primary school in Palembang is under the standard determined by The Ministry of Education and Culture (Kemendikbud). Hence, some ideas are formulated in Forum Group Discussion (FGD) namely the need of comprehensive training program and are continuously from the related institution, need of teacher’s supplementary book, and need of more action research on effective communication of teacher. Some indicators agreed for effective communication for teacher are (1) the importance of communication with students. (2) Competence and performance of teacher in communicating with the students. (3) Communication with the students in education. (4) Effective communication with the students. (5) Effective communication with students. (6) Obstacles in communication among the students in education. (7) Learning strategy that can build communication and cooperation among the students. (8) Communication with students in learning as educative interaction. The indicator will further be a reference in developing module for improvement of learning program in Universitas Terbuka.